Testing the moderating effect of openness to change and imposed change on employees’ readiness for converting commercial banks to Islamic banks - Abusloum, Mahmoud A S; Ahmad, Khaliq; Othman, Anwar Hasan Abdullah (Springer International Publishing, 2021)
The specific objective of this paper is to investigate the moderation effect of openness to change and nature of change (imposed or voluntary) on employees' readiness to convert to Islamic banking. Two studies were conducted to examine these effects. Study 1 was conducted to examine the moderation effect of openness to change on the relationship between involvement in the conversion process to Islamic banking and employees' readiness to convert to Islamic banking. To confirm the results of study 1, we inserted nature of change in study 2 as a moderator between openness to change and employees' readiness to convert to Islamic banking. By distributing 482 self-administered questionnaires to 12 public and private banks in Libya, a total of 316 valid responses were analysed. The findings showed that openness to change was statistically significant with full moderation effect whereas nature of change was a partial moderator with negative direction. This means that imposed change does not affect employees' readiness to convert to Islamic banking and regardless of the openness level of employees whether higher or lower. The results of this paper contribute to the body of literature of managing change especially the non-remarkable effect of the imposed change on employees' readiness for change as prior studies were showing the opposite. It is also contributing to the literature of conversion to Islamic banking as it is among the first studies that applied change theories. These findings may benefit central bank of Libya as well as banks' managers in implementing the conversion process smoothly and avoiding resistance to change.